DAMPAK KERUSUHAN MAKO BRIMOB MEI 2018 TERHADAP ABNORMAL RETURN INDEKS LQ45 YANG TERDAFTAR DI BEI - Guminto, Dewo Adhi; Marlina, Maria Assumpta Evi (Media Akuntansi dan Perpajakan Indonesia, 2019)
This research is an event study that aims to determine the differencein the average Abnormal return (AR) before, during, and after the MakoBrimob riot. The subject of this study is the LQ45 index company that hasfulfilled the criteria. The company does not conduct corporate actions suchas the announcement of stock split, right issue, merger & acquisition, anddividend in the observation period, which is five days before the riot, oneday during the riot (May 9, 2018) and five days after the riot. The results ofthe data normality test found that the data in this study were normallydistributed. P-value shows the number 0.412. The results of the differenttests using independent Sample T-Test (H1) showed no difference in theaverage abnormal return before, and during the Mako Brimob riots (ρ =0.050). The results of different tests using independent Sample T-Test (H2)were no difference in the average abnormal return during and after the incidentof the Mako Brimob riots (ρ = 0.117). The results of different testsusing Paired Sample T-Test (H3) were no difference in the average abnormalreturn before and after the incident of the Mako Brimob riots (ρ = 0.77).